EPID-08. IMPORTANCE OF THE INTERSECTION OF AGE AND SEX TO UNDERSTAND VARIATION IN INCIDENCE AND SURVIVAL FOR PRIMARY MALIGNANT GLIOMAS. (12th November 2021) - Wang, Gi-Ming; Cioffi, Gino; Patil, Nirav; Waite, Kristin; Lanese, Robert; Ostrom, Quinn; Kruchko, Carol; Berens, Michael; Connor, James; Lathia, Justin; Rubin, Joshua; Barnholtz-Sloan, Jill
Abstract: BACKGROUND: Gliomas are the most common type of malignant brain and other CNS tumors, accounting for 80.8% of malignant primary brain and CNS tumors. They cause significant morbidity and mortality. This study investigates the intersection between age and sex to better understand variation of incidence and survival for glioma in the United States. METHODS: Incidence data from 2000-2017 were obtained from the Central Crain Tumor Registry of the United States, which obtains data from the CDC's National Program of Cancer Registries and NCI's Surveillance Epidemiology and End Results Program (SEER), and survival data from the CDC's NPCR Registries. Age-adjusted incidence rates and rate ratios per 100, 000 were generated to compare male-to-female incidence by age group. Cox proportional hazard models were performed by age group, generating hazard ratios to assess male-to-female survival differences. RESULTS: Overall, glioma incidence was higher in males. Male-to-female incidence was lowest in ages 0-9 years (IRR: 1.04, 95% CI:1.01 - 1.07, p=0.003), increasing with age, peaking at 50-59 years (IRR:1.56, 95% CI: 1.53 - 1.59, p< 0.001). Females had worse survival for ages 0-9 (HR:0.93, 95% CI:0.87-0.99), though male survival was worse for all other age groups, with the difference highest in those 20-29 years (HR:1.36, 95% CI:1.28-1.44). Incidence and survival differences by age and sex also varied by histological subtype of glioma. CONCLUSION: To better understand the variation in glioma incidence and survival, investigating the intersection of age and sex is key. The current work shows that the combined impact of these variables is dependent on glioma subtype. These results contribute to the growing understanding of sex and age differences that impact cancer incidence and survival.